PERBANDINGAN TINGKAT KESUKARAN, DAYA PEMBEDA BUTIR SOAL DAN RELIABILITAS TES BENTUK PILIHAN GANDA BIASA DAN PILIHAN GANDA ASOSIASI MATA PELAJARAN EKONOMI - Nani Hanifah (Universitas Indraprasta PGRI, 2014)
The purpose of this research was to determine the difference of the item difficulty levels, the item discrimination powers, and the test reliabilities between the ordinary multiple choice (OMC) test and the association multiple choice (AMC) test. The population of the research was the second grade students of SLTPN 15 Bekasi, consisting 112 respondents. This quasi experimental research had utilized two group, randominized subjects post-test only design, using two treatments for each respondent, by giving them the OMC test and the AMC test after three week. The result of this research showed that the items difficulty levels of the AMC test was higher or the AMC test was more difficult than the OMC test. The research also indicated that the items discrimination powers of the AMC test was higher or the AMC test was more effective to differentiate between the higher ability testee and the lower ability testee than the items the OMC test. This research also indicated that not different test reliability between the AMC test and the OMC test.Keywords: the difficulty level, the discrimination power, the reliability test, the ordinary multiple choice (OMC), the association multiple choice (AMC).